Essential epidemiology : an introduction for students and health professionals - Webb, Penny, 1963-; Bain, Chris, 1947-; Page, Andrew, 1974- (Cambridge : Cambridge University Press, 2020)
Now in its fourth edition, Essential Epidemiology is an engaging and accessible introduction to the foundations of epidemiology. It addresses the study of infectious and chronic diseases, public health and clinical epidemiology, and the role of epidemiology in a range of health monitoring and research activities. Contemporary, historical and hypothetical examples enable students to engage with content, while mathematics is kept understandable with complex mathematics housed in optional material so the book remains accessible. With over ninety questions and answers to work through, this book is an essential resource for students, practitioners and anyone else who needs to interpret health data in their studies or work. Epidemiology's most important goal is to bring rigour to the collection, analysis and interpretation of health data to improve health on a global scale; Essential Epidemiology provides readers the tools to achieve that goal.
Title from publisher's bibliographic system (viewed on 07 Sep 2020).
Keywords: elektronické knihy; electronic books; Epidemiology